Acute abdominal aortic occlusion associated with transient paraplegia - Florent Porez, MD; Antoine Gaudin, MD; Dominique Fabre, MD, PhD; Alessandro Costanzo, MD; Lucas Le Guillou, MD; Stéphan Haulon, MD, PhD (Journal of Vascular Surgery Cases and Innovative Techniques)
We describe a rare case of acute occlusion of the abdominal aorta presenting as a rapidly evolving flaccid paraplegia owing to spinal cord ischemia and our management protocol that allowed complete recovery of the patient. A 70-year-old man who was referred to our department with painless lower limb loss of sensory and motor function. Endovascular recanalization was performed using a covered stent. The patient was discharged 4 days after the procedure with full recovery of neurological symptoms. Rapid aortic endovascular revascularization to restore flow to the pelvis and lower limbs, associated with spinal cord ischemia protocols, is critical for full recovery.